Vitamin D status in Sudanese pregnant women: a cross-sectional study. (4th July 2019) - Gaffer, Ahmed A; Rayis, Duria A; Elhussein, Osama G; Adam, Ishag
Abstract: Background: Maternal vitamin D deficiency is associated with maternal and perinatal adverse effects. This study was conducted to assess the vitamin D status among pregnant Sudanese women. Methods: A total of 180 pregnant women were enrolled in a cross-sectional study in Saad Abualila Hospital, Khartoum, Sudan. The medical history of each woman was collected and 25-hydroxyvitamin D [25(OH)D] was measured using an electrochemiluminescence immunoassay. Results: The median age, gravidity and gestational age was 27.7 y, 1.0 and 10.7 weeks, respectively. Of the 180 woman, 169 (93.9%) had vitamin D deficiency (≤20 ng/ml). There was no correlation between the 25(OH)D level and body mass index (r=−0.135, p=0.071) or haemoglobin level (r= 0.001, p=0.999). Conclusions: The current study showed a high prevalence of vitamin D deficiency. Further studies investigating the risk factors for vitamin D deficiency and the outcome of pregnancy are needed.